The effect of oil sands de-oiled asphalt on rheological properties, compatibility and stability of asphalt binder. (10th December 2020) - Pei, Xiaoguang; Fan, Weiyu; Liu, Yanjun; Qian, Chengduo; Wang, Yanfa; Jiang, Youshan; Chen, Song; Wang, Zhichao; Han, Ling
Graphical abstract: Highlights: OSDOA improves the rutting resistance but decreases the fatigue and low-temperature performance of base asphalt. OSDOA-modified asphalt has good storage stability. High aromatics and resins benefit rheological properties and compatibility. No new adsorption peaks appear during OSDOA modification. Thermal stability of base asphalt can be enhanced by OSDOA. Abstract: Oil sands de-oiled asphalt (OSDOA) has been utilized as an asphalt modifier. The purpose of this investigation was to evaluate the influence of OSDOA on the chemical composition, conventional properties, rheological properties, storage stability, compatibility, morphology and thermal stability of base asphalt. Experimental results revealed that saturates and aromatics decrease while resins and asphaltenes increase with increased OSDOA content, leading to higher colloidal instability index (CII) values. The addition of OSDOA significantly promotes resistance to high-temperature rutting but degrades the asphalt's fatigue resistance and low-temperature anti-cracking properties. It was found that OSDOA-modified asphalts have superior storage stability, and OSDOA is compatible with base asphalt due to its similar chemical composition and low ash content. High aromatics and resins of base asphalt are also beneficial to the rheological properties and storage stability. Furthermore, no new absorption peaks were identified from the addition of OSDOA. OSDOA can also strengthen the thermal stability of base asphalt. Consequently, OSDOA is a new modifier that enhances the performance of base asphalt in areas of rheological and compatibility behaviour. It has broad prospects for application due to its low-cost and high scale of production.